Proceedings of the Second International Symposium on Radiation Detectors and Their Uses (ISRD2018) 2019
DOI: 10.7566/jpscp.24.011025
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Dose Verification of High-Dose-Rate (HDR) Flattening Filter Free (FFF) Radiation Therapy by Using NIPAM Gel Dosimetry

Abstract: Flattening filter free (FFF) beam exhibits higher dose rate, lower head scatter photons, and less treatment time for patient than that of a flattened beam. The profile shape of the FFF beam is considerably sharper than that of the flattened beam due to the lack of flattening filter. However, the dose accuracy irradiated by the FFF beam should be investigated. In this study, a square irradiation field with 30 × 30 mm 2 was used for the two beam modes, namely, FFF and flattened beams. A three-dimensional N-isopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They found that the dynamic dose response was similar to the static, and the average sensitivity difference of fixed and movement NIPAM was 0.001 s-1/Gy [7]. NIPAM gel dosimeters have also been used in static measurement, such as the study by Yao et al in 2019. The results confirm that NIPAM gel dosimeter can be used for dose measurement of modern radiation technology [8].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…They found that the dynamic dose response was similar to the static, and the average sensitivity difference of fixed and movement NIPAM was 0.001 s-1/Gy [7]. NIPAM gel dosimeters have also been used in static measurement, such as the study by Yao et al in 2019. The results confirm that NIPAM gel dosimeter can be used for dose measurement of modern radiation technology [8].…”
Section: Introductionmentioning
confidence: 72%
“…NIPAM gel dosimeters have also been used in static measurement, such as the study by Yao et al in 2019. The results confirm that NIPAM gel dosimeter can be used for dose measurement of modern radiation technology [8]. However, most studies assume that the target treatment area is fixed, or the measurement of the calibration tube, and does not study the dynamic dose effect caused by physiological movement.…”
Section: Introductionmentioning
confidence: 83%